Split second [videorecording (Blu-Ray)] - Thompson, Gary Scott; Hauer, Rutger, 1944-2019; Cattrall, Kim; Duncan, Alastair, 1958-; Pollard, Michael J.; Armstrong, Alun; Postlethwaite, Pete; Tickner, Clive; Parsons, Stephen W.; Haines, Francis, 1957- (MVD rewind collection, 2020)
In a flooded, dystopian future, Detective Harley Stone hunts a swift, sharp-clawed, deadly, and possibly non-human, serial killer who murdered his partner and has haunted him ever since.